Faktor- Faktor yang Mempengaruhi Permintaan Daging Ayam Kampung di Pasar Tradisional Kota Surakarta - Digna Puspa Amelia; Sutrisno Hadi Purnomo; Sudiyono Sudiyono (Universitas Sebelas Maret (UNS), 2018)
This research aimed to find out the factors affecting the demand for free-range chicken meat among consumers and to find out the difference of demand between one consumer group and another by demographic characteristics of consumers in traditional markets of Surakarta City. This research was conducted from August 24 to September 21, 2017 in traditional markets of Surakarta City using survey method. This study was a descriptive and associative research. Respondents were 60 (sixty) buyers of free-range chicken meat selected using convenience sampling method. The data obtained consisted of primary and secondary ones. Primary data included demographic characteristics (income, age, education, and family member number), free-range chicken meat price, and broiler chicken meat price. Secondary data included data from Animal Husbandry Service, Central Statistic Bureau, and literature. Data analysis was carried out using a multiple linear regression analysis, followed with determinacy test (R2), F test, t-test and One-way Anova test. From the multiple linear regression analysis, the following equation was obtained = Y = 4.811 – 2.443X1- 4.366X2- 0.038X3+ 5.503X4- 0.248X5- 0.197X6+ 1.518. R2 value was 0.593, meaning that all independent variables affected dependent variable (demand for free-range chicken meat) by 59.3%. The result of Ftest showed Fstatistic12.876 > Ftable 2.275, meaning that H0 was not supported, indicating that independent variables affected simultaneously the dependent one. The result of t test and One-way Anova test showed that age and income partially (individually) affected significantly the demand for free-range chicken meat. The conclusion of research was that all variables affected simultaneously the demand for free-range chicken meat, and age and income factors individually showed the difference of demand for free-range chicken meat in traditional market of Surakarta City.